Youth Farmer Regeneration: Social Networks in Klaten's Farming Community from a Risk Society Theory - Umaruddin, Muhammad; Julfadlina, Chairunnisa (Universitas Tanjungpura, 2025)
This study aims to analyze the role of social networks in Komunitas Petani Muda Klaten (KPMK) in promoting the regeneration of young farmers by enhancing interaction, collaboration, and support among community members. Using the risk society theory framework, it examines efforts to reduce uncertainties and risks related to land access, capital, and technology faced by youth in the agricultural sector. The research employs a mixed-methods approach, integrating qualitative and quantitative analyses to comprehensively understand KPMK dynamics. Digital data from online articles and YouTube videos were collected, supplemented by interviews and online surveys. Qualitative data were thematically analyzed using Atlas.ti, while quantitative data were processed descriptively via Microsoft Excel. Findings reveal that young farmers in Klaten face serious economic and social challenges, including high production costs, limited access to modern agricultural technology, and negative stigma toward farming as a profession. KPMK plays a critical role in mitigating these risks by providing access to capital, training, and marketing networks, while strengthening social support and solidarity among members through technology and social media. The community positively impacts agricultural sustainability and youth engagement by leveraging social networks for information exchange, collaboration, and mutual support. Through training, sustained mentoring, and strategic partnerships with stakeholders, KPMK enhances social cohesion, technical knowledge, and access to agricultural resources and technology. However, challenges such as insufficient intensive mentoring and reliance on external support must be addressed to ensure long-term sustainability.